Cover Image, Volume 138, Issue 32. Issue 32 (17th May 2021) - Zhang, Na; Yan, Tingting; Li, Chunhui; Deng, Huining; Li, Zhenhua; Yu, Ru; Wang, Tiejun; Xu, Shicai; Li, Qiang; Wang, Jihua
Abstract : The cover designed by Li Qiang and colleagues shows how a series of polyamide thin‐film nanocomposite (PA TFN) membranes have been fabricated by incorporating hydrophilic poly(dopamine) (PDA) coated carbon nanotubes (CNTs@PDA) into the PA selective layer via interfacial polymerization. The desalination performance is obviously influenced by the coating thickness of PDA and the loading concentration of PDA@CNTs. The PDA coating makes the surface of PA TFN membrane more hydrophilic, smoother and less electronegative, leading to better anti‐fouling property and separation performance durability of PA TFN membranes. DOI: 10.1002/app.50808